White coating, reflective film, preparation method of reflective film and solar cell module
By using white coatings prepared with materials such as modified acrylate and rutile titanium dioxide, a reflective film with excellent insulation performance, moisture and heat resistance and high reflectivity is formed, which solves the problems of the risk of insulation of reflective films, poor moisture and heat resistance and high manufacturing cost in the prior art, and improves the performance and efficiency of solar cell modules.
Patent Information
- Application Number
- CN202510005048.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-25
AI Technical Summary
The reflective films of existing solar cell modules have problems such as risk of insulation, poor moisture and heat resistance and high manufacturing costs, and it is difficult to effectively utilize the sunlight in the gap between the battery strings.
A white coating including modified acrylate, rutile titanium dioxide, dispersant, coupling agent, initiator and curing agent is used, and thermally cured by imprinting and photocuring to form a reflective film with excellent insulation properties, moisture and heat resistance and high reflectivity.
The high reflectivity, good insulation performance and humidity resistance of the reflective film are achieved, while reducing manufacturing costs and improving the power and energy density of the solar cell module.
Smart Images

Figure CN119875492A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of solar cells, and specifically relates to a white coating, a reflective film and a preparation method thereof, and a solar cell assembly. Background Art
[0002] In the production of solar cell modules, gaps are reserved between the cell strings to prevent the cells from being connected in parallel. The area of the gaps accounts for about 2.8-3% of the module area. By making good use of the sunlight in the gaps, the power of the solar cell modules can be increased, thereby achieving a higher energy density of the photovoltaic modules. The existing technology usually applies a thin film material containing a metal coating to the back glass of the gap between the cells or the cell strings to increase the power of the module, but this is prone to the situation where the metal coating directly contacts the cells and conductive solder and other materials, resulting in a short circuit and a decrease in the power of the module; at the same time, during the application process of the metal reflective layer, the aluminum coating is soft and is easily scratched and corroded, affecting its reflective effect.
[0003] In order to overcome this defect, researchers designed a reflective film that improves photovoltaic conversion efficiency, including a substrate layer and an adhesive layer disposed under the substrate layer, a microstructure layer disposed on the substrate layer, and a reflective layer on the microstructure layer. The reflective layer is an aluminum-plated layer or a silver-plated layer, but there is an insulation risk. At the same time, after being exposed to moisture and heat, the adhesion between the aluminum layer and the prism layer deteriorates, and the reflectivity decreases. The related technology applies a layer of resin insulation layer on the basis of the aluminum-plated layer, but the gain rate decreases, and the microprism layer does not play a focusing advantage. At the same time, the manufacturing cost is high.
[0004] Therefore, developing a reflective film with no insulation risk and low cost is a technical problem to be solved urgently in this field. Summary of the invention
[0005] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application proposes a white coating with high reflectivity, excellent insulation performance, good moisture and heat resistance or low cost, a reflective film and a preparation method thereof, and a solar cell module.
[0006] In the first aspect of the present application, a white coating is proposed, comprising: 15 to 25 parts by weight of a modified acrylate, 5 to 10 parts by weight of a monomer containing a double bond function, 75 to 85 parts by weight of rutile titanium dioxide, 2 to 5 parts by weight of a dispersant, 1 to 2 parts by weight of a coupling agent, 4 to 6 parts by weight of an initiator and 3 to 5 parts by weight of a curing agent.
[0007] The use of the above formula to prepare the reflective film can improve the insulation performance, moisture and heat resistance and reflectivity of the reflective film.
[0008] In some embodiments, the rutile titanium dioxide comprises rutile titanium dioxide coated with at least one of silicon dioxide, aluminum oxide, and zirconium oxide, thereby improving the reflectivity and weather resistance of the reflective film.
[0009] In some embodiments, the monomer includes at least one of 1,6-hexanediol diacrylate (HDDA), trimethylolpropane triacrylate (TMPTA), isobornyl acrylate (IBOA), and propionyl morpholine (AMCO); in other embodiments, the monomer includes 1,6-hexanediol diacrylate and propionyl morpholine.
[0010] In some embodiments, the dispersant includes a high molecular weight acrylic block copolymer solution containing a carboxyl group, thereby improving the dispersibility of the white coating.
[0011] In some embodiments, the coupling agent includes at least one of amino siloxane and epoxy siloxane, thereby improving the adhesion and moisture and heat resistance of the micro-prism layer.
[0012] In some embodiments, the initiator includes at least one of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide (TPO), bis-2,6-difluoro-3-pyrrolophenyl titanocene (784), phenyl (2,4,6-trimethylphenyl acyl) phosphine oxide (819), 2,4-diethylthioxanthene-9-one (DETX), 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyloxime) (OXE-2); in other embodiments, the initiator includes an acylphosphine oxide photoinitiator and a titanocene initiator. This can more effectively initiate curing, which is conducive to complete curing of the white coating.
[0013] In some embodiments, the curing agent includes at least one of 1,6-hexane diisocyanate (HDI), dicyclohexylmethane diisocyanate (HMDI), hydrogenated xylylene diisocyanate (HXDI), and isophorone diisocyanate (IPDI); in other embodiments, the curing agent is 1,6-hexane diisocyanate (HDI). This can increase the curing rate.
[0014] In some embodiments, the white paint further comprises: at least one of a plasticizer, a defoamer, a flame retardant and a leveling agent, thereby further improving the comprehensive performance of the white paint.
[0015] The second aspect of the present application provides a reflective film, which includes: a base layer and a microprism layer, wherein the microprism layer is arranged on at least one side of the base layer. Therefore, the reflective film has excellent insulation performance, moisture and heat resistance and reflectivity.
[0016] In some embodiments, the micro-prismatic layer is formed by curing the white coating described above.
[0017] In some embodiments, the thickness of the micro-prism layer is 8 μm to 10 μm, thereby further improving the reflectivity of the reflective film.
[0018] In some embodiments, the angle between the ridgeline of the microprism layer and the length direction of the base layer is 30° to 60°; in other embodiments, the angle between the ridgeline of the microprism layer and the length direction of the base layer is 45°. This can further improve the reflectivity of the reflective film.
[0019] In some embodiments, the base layer has a thickness of 40 μm to 60 μm.
[0020] In some embodiments, the base layer is preferably white, thereby increasing the reflectivity of the reflective film.
[0021] In some embodiments, the material of the base layer includes polyethylene terephthalate (PET).
[0022] In some embodiments, the reflective film further includes an adhesive film layer, and the adhesive film layer is disposed on a side of the base layer away from the micro-prism layer.
[0023] The third aspect of the present application provides a method for preparing a reflective film, comprising: printing the white coating described in the first aspect of the present application on a base layer, and obtaining a micro-prism layer after photocuring and thermal curing.
[0024] In some embodiments, the energy of the photocuring is 220 mj to 300 mj.
[0025] In some embodiments, the thermal curing temperature is 40° C. to 50° C., and the curing time is 24 h to 36 h.
[0026] In some embodiments, the method further includes: disposing an adhesive film layer on a side of the base layer away from the microprism layer.
[0027] The above method of the present application has a simple preparation process, reduces the processing steps, and has low cost, which is conducive to industrial production.
[0028] The fourth aspect of the present application provides a solar cell assembly, comprising the reflective film described in the second aspect of the present application or the reflective film prepared by the method described in the third aspect of the present application. Thus, the solar cell assembly has higher power and energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a structural diagram of an embodiment of the present application.
[0030] Figure 2 It is a structural diagram of an embodiment of the present application.
[0031] Reference numerals:
[0032] 1-matrix layer; 2-microprism layer; 3-film layer. DETAILED DESCRIPTION
[0033] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0034] In the first aspect of the present application, a white coating is proposed, comprising: 15 to 25 parts by weight of a modified acrylate, 5 to 10 parts by weight of a monomer containing a double bond function, 75 to 85 parts by weight of rutile titanium dioxide, 2 to 5 parts by weight of a dispersant, 1 to 2 parts by weight of a coupling agent, 4 to 6 parts by weight of an initiator and 3 to 5 parts by weight of a curing agent.
[0035] The use of the above formula to prepare reflective film can improve the insulation performance, moisture and heat resistance and reflectivity of the reflective film. The rutile titanium dioxide in the white paint absorbs the ultraviolet band and reflects the visible band and near-infrared band. It can be imprinted on one side of the reflective film substrate layer to form a micro-prism structure. By using the micro-prism focusing principle, the ridgeline and the length direction of the substrate layer present a certain angle, and the light is reflected and refracted multiple times, which can effectively improve the reflectivity of the reflective film; and the use of modified acrylic ester as the resin material is conducive to improving the insulation performance of the reflective film.
[0036] In some embodiments, the rutile titanium dioxide includes rutile titanium dioxide coated with at least one of silicon dioxide, aluminum oxide, and zirconium oxide. This can improve the reflectivity and weather resistance of the reflective film. As an example, the model of the rutile titanium dioxide can be Chemours Chemical R706. In some specific examples, the amount of titanium dioxide added is 75 to 85 parts by weight, for example, 75 parts by weight, 76 parts by weight, 77 parts by weight, 78 parts by weight, 79 parts by weight, 80 parts by weight, 81 parts by weight, 82 parts by weight, 83 parts by weight, 84 parts by weight or 85 parts by weight. If too much titanium dioxide is added, the coating is too brittle and easy to fall off; if too little titanium dioxide is added, the reflectivity of the coating is low.
[0037] In some embodiments, the modified acrylate can be a hydroxyl-terminated polyurethane acrylate, which is synthesized by a two-step method using polyether polyol, hydroxy acrylate, and isophorone diisocyanate IPDI as raw materials. Its structure contains C=C double bonds and hydroxyl groups, and can be UV-cured or thermally cured, which is conducive to the complete curing of white paint and overcomes the problems of incompatibility of system components and uneven local curing. The resin has good flexibility and adhesion, a glass transition temperature Tg of 15°C to 30°C, a molecular weight of 8000g / mol to 15000g / mol (such as 8000g / mol, 9000g / mol, 10000g / mol, 11000g / mol, 12000g / mol, 13000g / mol, 14000g / mol or 15000g / mol, etc.), and an addition amount of 15 to 25 parts by weight (such as 15 parts by weight, 18 parts by weight, 20 parts by weight, 22 parts by weight or 25 parts by weight, etc.). If the amount added is too much, the micro-prismatic layer will be too soft, resulting in the surface of the reflective film being easily scratched during the production of solar cell modules, and the micro-prismatic layer structure being damaged, affecting reflection; if the amount added is too little, the coating will cure slowly, resulting in difficulty in forming the micro-prismatic layer. As an example, the resin model may be Changxing Chemical A892.
[0038] In some embodiments, the monomer includes at least one of 1,6-hexanediol diacrylate (HDDA), trimethylolpropane triacrylate (TMPTA), isobornyl acrylate (IBOA), and propionyl morpholine (AMCO); in other embodiments, the monomer includes 1,6-hexanediol diacrylate and propionyl morpholine.
[0039] In some embodiments, the dispersant includes a high molecular weight acrylic block copolymer solution containing a carboxyl group. As an example, the dispersant may be BYK-110. This can improve the dispersibility of the white paint.
[0040] In some embodiments, the coupling agent includes at least one of aminosiloxane and epoxysiloxane. Such coupling agents have good wetting and dispersibility for fillers and can improve the adhesion and moisture and heat resistance of the coating. As an example, the model of the coupling agent can be Zhijiang Organosilicon γ-aminopropyl triethoxysilane KH5550.
[0041] In some embodiments, the initiator includes at least one of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide (TPO), bis-2,6-difluoro-3-pyrrolophenyl titanocene (784), phenyl (2,4,6-trimethylphenyl acyl) phosphine oxide (819), 2,4-diethylthioxanthene-9-one (DETX), and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetoximate) (OXE-2); in other embodiments, the initiator includes acylphosphine oxide photoinitiators and titanocene initiators, both of which have significant absorption capacity in the ultraviolet and visible light regions. For a coating system containing a pigment (i.e., rutile titanium dioxide), it can more effectively initiate curing, and no yellowing occurs after curing and under long-term light radiation, which is conducive to the thorough curing of the thick film. In some specific examples, the amount of initiator added is 5 to 8 parts by weight, for example, 5 parts by weight, 6 parts by weight, 7 parts by weight or 8 parts by weight. If the amount of initiator added is too much, the residual amount of initiator is large and the coating is prone to yellowing; if the amount of initiator added is too little, the initiator concentration is insufficient, the coating cures too slowly, and it is difficult to form a micro-prismatic structure layer. As an example, the model of the initiator can be BASF 819, 784.
[0042] In some embodiments, the curing agent includes at least one of 1,6-diisocyanate hexane (HDI), dicyclohexylmethane diisocyanate (HMDI), hydrogenated diisocyanate (HXDI), and isophorone diisocyanate (IPDI); in other embodiments, the curing agent is 1,6-diisocyanate hexane (HDI), and its NCO content is 30% to 33% (such as 30%, 31%, 32% or 33%, etc.), and the NCO content refers to the content of isocyanate groups (NCO) in the compound, and the testing method is the di-n-butylamine titration method known in the industry, thereby allowing more effective curing.
[0043] In some embodiments, the white coating further comprises: at least one of a plasticizer, a defoamer, a flame retardant and a leveling agent. For example, the plasticizer may be di(2-ethylhexyl) phthalate (DEHP), butyl benzyl phthalate (BBP), diethyl phthalate (DEP), etc., the defoamer may be propylene oxide, ethylene oxide, tributyl phosphate, etc., and the leveling agent may be polydimethylsiloxane, an acrylate leveling agent or a fluorine leveling agent, etc. This can further improve the comprehensive performance of the white coating.
[0044] The second aspect of the present application provides a reflective film, referring to Figure 1The reflective film includes: a base layer 1; a microprism layer 2, and the microprism layer is arranged on at least one side of the base layer. The mechanism of action of the present application is that the pigment in the white paint is rutile titanium dioxide, which absorbs the ultraviolet band and reflects the visible band and near-infrared band. Utilizing the principle of microprism focusing, the ridgeline presents a certain angle with the length direction of the base layer, and the light is reflected and refracted multiple times, and part of the light transmitted to the base layer is reflected again. The reflectivity of the reflective film in the 400-1200nm band is more than 80%. When applied to solar cell modules, the directional reflection line is obvious and the gain effect is significant. At the same time, the solar cell modules have no insulation risks.
[0045] In some embodiments, the micro-prismatic layer is formed by curing the white coating described above.
[0046] In some embodiments, the thickness of the micro-prism layer is 8 μm to 10 μm, for example, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm. Figure 1 The thickness of the micro-prism layer is the height h of the triangle in the figure. The thickness of the micro-prism layer within the above range is beneficial to improving the reflectivity of the reflective film.
[0047] In some embodiments, the angle between the ridgeline of the microprism layer and the length direction of the base layer is 30° to 60°, for example, 30°, 40°, 50° or 60°, etc. In other embodiments, the angle between the ridgeline of the microprism layer and the length direction of the base layer is 45°. This can further improve the reflectivity of the reflective film.
[0048] In some embodiments, the thickness of the base layer is 40 μm to 60 μm, for example, 40 μm, 45 μm, 50 μm, 55 μm or 60 μm.
[0049] In some embodiments, the base layer is white, thereby increasing the reflectivity of the reflective film.
[0050] In some embodiments, the material of the base layer includes polyethylene terephthalate (PET).
[0051] In some embodiments, the reflective film further includes an adhesive film layer 3, which can be specifically referred to Figure 2 The adhesive film layer is arranged on a side of the base layer away from the micro-prism layer.
[0052] The third aspect of the present application provides a method for preparing a reflective film, comprising: printing the white coating described in the first aspect of the present application on a base layer, and obtaining a micro-prism layer after photocuring and thermal curing.
[0053] Specifically, the white coating can be evenly printed on the base layer, and then double-sided photocuring is performed and then thermal curing is performed to ensure complete curing, thereby forming a micro-prism layer.
[0054] In some embodiments, the energy of the photocuring is 220mj to 300mj. If ultraviolet light is used, the energy can be 220mj, 230mj, 240mj, 250mj, 260mj, 270mj, 280mj, 290mj or 300mj.
[0055] In some embodiments, the thermal curing temperature is 40°C to 50°C (such as 40°C, 45°C or 50°C, etc.), and the time is 24h to 36h (such as 24h, 26h, 28h, 30h, 32h, 34h or 36h, etc.).
[0056] In some embodiments, the method further includes: disposing an adhesive film layer on a side of the base layer away from the microprism layer.
[0057] The above method of the present application has a simple preparation process, reduces the processing steps, and has low cost, which is conducive to industrial production.
[0058] The fourth aspect of the present application provides a solar cell assembly, comprising the reflective film described in the second aspect of the present application or the reflective film prepared by the method described in the third aspect of the present application. Thus, the solar cell assembly has higher power and energy density.
[0059] The embodiments of the present application are described in detail below.
[0060] Example 1
[0061] According to the required number of parts of the formula in Table 1, A892, HDDA, IBOA, and BYK-110 were mixed and stirred for 15 minutes, rutile titanium dioxide was slowly added, and stirred at high speed for 30 minutes. The mixture was ground with a horizontal grinder until the average particle size was less than 0.5 μm. While stirring, coupling agent KH5550, initiators 819 and 784, and curing agent HDI were slowly added, and stirred for 20 minutes to obtain a white coating liquid. The coating liquid was coated on a transparent BOPET film with a thickness of 50 μm by an imprint coating method. The thickness of the microprism layer was 8 μm, the vehicle speed was 10 m / min, double-sided UV curing, and thermal curing at 40°C for 24 hours. A 70 μm thick EVA film was applied to the back, and the film was cut into strips to complete the preparation of the reflective film sample.
[0062] Example 2
[0063] According to the required number of parts of the formula in Table 1, A892, HDDA, IBOA, and BYK-110 were mixed and stirred for 15 minutes, rutile titanium dioxide was slowly added, and stirred at high speed for 30 minutes. The mixture was ground with a horizontal grinder until the average particle size was less than 0.5 μm. While stirring, coupling agent KH5550, initiators 819 and 784, and curing agent HDI were slowly added, and stirred for 20 minutes to obtain a white coating liquid. The coating liquid was coated on a transparent BOPET film with a thickness of 50 μm by an imprint coating method. The thickness of the microprism layer was 10 μm, the vehicle speed was 10 m / min, double-sided UV curing and thermal curing at 40°C for 24 hours, and a 70 μm thick EVA film was applied to the back, and the film was cut into strips to complete the preparation of the reflective film sample.
[0064] Example 3
[0065] According to the required number of parts of the formula in Table 1, A892, HDDA, IBOA, and BYK-110 were mixed and stirred for 15 minutes, rutile titanium dioxide was slowly added, and stirred at high speed for 30 minutes. The mixture was ground with a horizontal grinder until the average particle size was less than 0.5 μm. While stirring, coupling agent KH5550, initiators 819 and 784, and curing agent HDI were slowly added, and stirred for 20 minutes to obtain a white coating liquid. The coating liquid was coated on a transparent BOPET film with a thickness of 50 μm by an imprint coating method. The thickness of the microprism layer was 9 μm, the vehicle speed was 10 m / min, double-sided UV curing, and thermal curing at 40°C for 24 hours. A 70 μm thick EVA film was applied to the back, and the film was cut into strips to complete the preparation of the reflective film sample.
[0066] Example 4
[0067] According to the required number of parts of the formula in Table 1, A892, HDDA, IBOA, and BYK-110 were mixed and stirred for 15 minutes, rutile titanium dioxide was slowly added, and stirred at high speed for 30 minutes. The mixture was ground with a horizontal grinder until the average particle size was less than 0.5 μm. While stirring, coupling agent KH5550, initiators 819 and 784, and curing agent HDI were slowly added, and stirred for 20 minutes to obtain a white coating liquid. The coating liquid was coated on a transparent BOPET film with a thickness of 50 μm by an imprint coating method. The thickness of the microprism layer was 8.5 μm. The vehicle speed was 10 m / min, double-sided UV curing and thermal curing at 40°C for 24 hours were performed, and a 70 μm thick EVA film was applied to the back, and the film was cut into strips to complete the preparation of the reflective film sample.
[0068] Example 5
[0069] According to the required number of parts of the formula in Table 1, A892, TMPTA, and BYK-110 were mixed and stirred for 15 minutes, rutile titanium dioxide was slowly added, and stirred at high speed for 30 minutes. The mixture was ground with a horizontal grinder until the average particle size was less than 0.5 μm. While stirring, coupling agent KH5550, initiator TPO, and curing agent HMDI were slowly added and stirred for 20 minutes to obtain a white coating liquid. The coating liquid was coated on a transparent BOPET film with a thickness of 40 μm by an imprint coating method. The thickness of the microprism layer was 8 μm. The vehicle speed was 10 m / min, double-sided UV curing and thermal curing at 40°C for 24 hours were performed, and a 70 μm thick EVA film was applied to the back, and the film was cut into strips to complete the preparation of the reflective film sample.
[0070] Comparative Example 1
[0071] Acrylic resin was embossed and coated on a 50 μm thick transparent BOPET base film to form a microstructure coating, and then vacuum-plated with aluminum. A 70 μm thick EVA adhesive layer was sprayed on the other side of the base film and cut to form a reflective film sample.
[0072] Comparative Example 2
[0073] A 50 μm thick transparent BOPET base film was vacuum-plated with aluminum, and a 70 μm thick EVA adhesive layer was coated on the other side of the base film, which was then cut to form a reflective film sample.
[0074] Table 1 White paint formula composition
[0075]
[0076] The above samples were tested as follows:
[0077] 1. Reflectivity: Test method refers to IEC-62805-2;
[0078] 2. Microprism layer resistivity: test method refers to GB / T3048.5-2007;
[0079] 3. Adhesion: The test method refers to GB / T9286-1998 "Coating Adhesion Grade, Sample Preparation and Test";
[0080] 4. Vertex angle: The test method refers to ISO 9220:2022 "Measurement of coating thickness. Scanning electron microscopy method";
[0081] 5. Peel strength: The test method refers to GB / T2790 "Adhesive 180 peel strength test method flexible material to rigid material";
[0082] 6. Yellowing: The test method refers to the peeling force and color difference changes in the standard GB / T2423.3 "High and Low Temperature and Humidity Test Method";
[0083] 7. Thermal oxygen test: Refer to the hot spot test for reflectivity changes in the standard IEC61215:2005 "Design, identification and characterization of terrestrial crystalline silicon photovoltaic modules".
[0084] The test results are as follows:
[0085] Table 2 Test results
[0086]
[0087] It can be seen from Table 2 that, compared with the comparative examples, the reflective film of the embodiment samples involved in the present application has excellent insulation and good moisture and heat resistance, and at the same time has a low cost, which is conducive to market promotion and application.
[0088] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0089] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A white paint, characterized in that: include: 15 to 25 parts by weight of modified acrylate, 5 to 10 parts by weight of monomer containing double bond function, 75 to 85 parts by weight of rutile titanium dioxide, 2 to 5 parts by weight of dispersant, 1 to 2 parts by weight of coupling agent, 4 to 6 parts by weight of initiator and 3 to 5 parts by weight of curing agent.
2. The white paint according to claim 1, characterized in that: Satisfy at least one of the following conditions: The rutile titanium dioxide comprises rutile titanium dioxide coated with at least one of silicon dioxide, aluminum oxide and zirconium oxide; The monomers include at least one of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, isobornyl acrylate, and propionyl morpholine, preferably 1,6-hexanediol diacrylate and propionyl morpholine; The dispersant includes a high molecular weight acrylic block copolymer solution containing carboxyl groups; The coupling agent includes at least one of amino siloxane and epoxy siloxane; The initiator includes at least one of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, bis-2,6-difluoro-3-pyrrolophenyl titanocene, phenyl (2,4,6-trimethylphenyl acyl) phosphine oxide, 2,4-diethylthioxanthene-9-one, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyl oxime), preferably an acylphosphine oxide photoinitiator and a titanocene initiator; The curing agent includes at least one of 1,6-hexane diisocyanate, dicyclohexylmethane diisocyanate, hydrogenated xylylene diisocyanate, and isophorone diisocyanate, and is preferably 1,6-hexane diisocyanate.
3. The white paint according to claim 1, characterized in that: The white paint further comprises: at least one of a plasticizer, a defoamer, a flame retardant and a leveling agent.
4. A reflective film, characterized in that: include: Base layer; A micro-prism layer is disposed on at least one side of the base layer.
5. The reflective film according to claim 4, characterized in that: The microprism layer is formed by curing the white paint according to claims 1 to 3.
6. The reflective film according to claim 4, characterized in that: Satisfy at least one of the following conditions: The thickness of the microprism layer is 8 μm to 10 μm; The angle between the ridgeline of the microprism layer and the length direction of the substrate layer is 30° to 60°, preferably 45°; The thickness of the substrate layer is 40 μm to 60 μm; The color of the base layer is preferably white; The material of the base layer includes polyethylene terephthalate.
7. The reflective film according to claim 4, characterized in that: The reflective film further comprises an adhesive film layer, and the adhesive film layer is arranged on a side of the base layer away from the micro-prism layer.
8. A method for preparing the reflective film according to any one of claims 4 to 7, characterized in that: include: The white coating according to any one of claims 1 to 3 is printed on a base layer, and then photocured and thermally cured to obtain a microprism layer.
9. The method according to claim 8, characterized in that The energy of the photocuring is 220mj to 300mj; and / or The thermal curing temperature is 40°C to 50°C and the time is 24h to 36h; and / or An adhesive film layer is arranged on a side of the base layer away from the micro-prism layer.
10. A solar cell module, characterized in that: The invention comprises the reflective film according to any one of claims 4 to 7 or the reflective film prepared by the method according to any one of claims 8 to 9.
Citation Information
Cited By
Reflective film based on high refractive index resin
CN120871315A